2014
DOI: 10.9790/0837-19179096
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ownership Concentration on Firm Value of Listed Companies

Abstract: Abstract:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…The present work followed prior studies and evaluated board characteristics in terms of board size (Rahman and Saima, 2018; Nepal and Deb, 2021), board independence (Vintila and Gherghina, 2013; Khan et al , 2017) and board diversity (Tarigan et al , 2018; Ararat and Sayedy, 2019). We evaluated ownership characteristics based on ownership concentration (Oluwagbemiga et al , 2014; Busta et al , 2014) and CEO ownership (Sugosha and Artini, 2020; Syamsudin et al , 2020). Board size is measured by the natural logarithm of the number of directors on the board.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work followed prior studies and evaluated board characteristics in terms of board size (Rahman and Saima, 2018; Nepal and Deb, 2021), board independence (Vintila and Gherghina, 2013; Khan et al , 2017) and board diversity (Tarigan et al , 2018; Ararat and Sayedy, 2019). We evaluated ownership characteristics based on ownership concentration (Oluwagbemiga et al , 2014; Busta et al , 2014) and CEO ownership (Sugosha and Artini, 2020; Syamsudin et al , 2020). Board size is measured by the natural logarithm of the number of directors on the board.…”
Section: Methodsmentioning
confidence: 99%
“…Bubbico et al (2012) showed that ownership concentration has a positive effect on the firm value of financial institutions listed on the Italian Stock Exchange and stated that high concentration is expected to produce high monitoring exercised by majority shareholders over the management to maximize firm value. Moreover, Oluwagbemiga et al (2014) indicated a positive effect of ownership concentration on the firm value of banks listed on the Nigeria Stock Exchange. However, Thompson et al (2016) found a positive and non-significant relationship between ownership concentration and firm value.…”
Section: Ownership Concentration and Firm Valuementioning
confidence: 97%
“…Hasil pengujian yang dilakukan dengan menggunakan EViews 11 menunjukkan bahwa kepemilikan terkonsentrasi memiliki nilai probabilitas sebesar 0,1445 yang lebih besar dari nilai signifikansi yakni 0,1445 > 0,05, maka H 5 ditolak artinya kepemilikan terkonsentrasi tidak berpengaruh terhadap nilai perusahaan. Hasil yang didapatkan pada penelitian ini menolak kesimpulan dari penelitian yang telah dilakukan oleh Kong, Famba, Chituku-Dzimiro, Sun, & Kurauone (2020), Oluwagbemiga, Michael, & Zaccheaus (2014), dan Vintilă & Gherghina (2014) yang menyatakan bahwa kepemilikan terkonsentrasi berpengaruh terhadap nilai perusahaan.…”
Section: Pengaruh Kepemilikan Terkonsentrasi Terhadap Nilai Perusahaanunclassified
“…Pemegang saham dominan dapat memengaruhi kinerja operasional perusahaan dalam mengambil keputusan-keputusan strategis yang memaksimalkan perilaku perusahaan untuk tujuan ekonomi (Utomo et al, 2019). Pemegang saham mayoritas cenderung membuat area mereka sendiri untuk mencegah terbentuknya pemegang saham mayoritas lain tersebut (Oluwagbemiga et al, 2014). Jika pemilik saham mayoritas ingin meningkatkan nilai pasar perusahaan, kepemilikan terkonsentrasi dapat menerapkan fungsi pengawasan yang lebih banyak, mengurangi agency costs, profit dan harga saham yang lebih tinggi, karena pemegang saham mayoritas memiliki wewenang yang lebih kuat untuk mengawasi perusahaan dan penyelarasan insentif yang lebih besar antara pemilik dengan manajer (Pedersen & Thomsen, 2003).…”
Section: Pendahuluanunclassified